2021
DOI: 10.3390/cancers13235920
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Targeting of CXCR4—New Horizons

Abstract: Given its pre-eminent role in the context of tumor cell growth as well as metastasis, the C-X-C motif chemokine receptor 4 (CXCR4) has attracted a lot of interest in the field of nuclear oncology, and clinical evidence on the high potential of CXCR4-targeted theranostics is constantly accumulating. Additionally, since CXCR4 also represents a key player in the orchestration of inflammatory responses to inflammatory stimuli, based on its expression on a variety of pro- and anti-inflammatory immune cells (e.g., m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 99 publications
0
20
0
Order By: Relevance
“…Indeed, the murine CXCR4 has limited homology with human CXCR4 and a modification of MK007 for human CXCR4 may be needed. Nevertheless, our data from in vitro studies and first clinical data on a patient with multiple myeloma (MM) using a new CXCR4-targeted Tc ligand ( 99m Tc; based on the structure of MK007) for SPECT/CT imaging [ 34 ] are encouraging for the potential clinical use of a modified MK007. Indeed, the ligand accumulated in intramedullary MM lesions and no high accumulation was observed in the liver, in contrast to mice [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the murine CXCR4 has limited homology with human CXCR4 and a modification of MK007 for human CXCR4 may be needed. Nevertheless, our data from in vitro studies and first clinical data on a patient with multiple myeloma (MM) using a new CXCR4-targeted Tc ligand ( 99m Tc; based on the structure of MK007) for SPECT/CT imaging [ 34 ] are encouraging for the potential clinical use of a modified MK007. Indeed, the ligand accumulated in intramedullary MM lesions and no high accumulation was observed in the liver, in contrast to mice [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our data from in vitro studies and first clinical data on a patient with multiple myeloma (MM) using a new CXCR4-targeted Tc ligand ( 99m Tc; based on the structure of MK007) for SPECT/CT imaging [ 34 ] are encouraging for the potential clinical use of a modified MK007. Indeed, the ligand accumulated in intramedullary MM lesions and no high accumulation was observed in the liver, in contrast to mice [ 34 ]. Furthermore, we have not yet determined the affinity of MK007 for the murine CXCR4 receptor and the specificity of MK007 in the IL1B model.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the above immunostimulators, the CXCR4 was associated with both LOX and LOXL3. It is expressed on various pro-and anti-inflammatory immune cells, especially in macrophages and T cells (101). Multiple drugs targeted on CXCR4 have been under investigation (102).…”
Section: Discussionmentioning
confidence: 99%
“…6 Therefore, in vivo quantification of CXCR4 expression using CXCR4-targeted PET/CT imaging has received some consideration. [7][8][9] Recently, a growing literature has reported that 68 Ga-pentixafor PET/CT plays an important role in the diagnosis of some tumors and inflammation. [10][11][12] It has now been demonstrated that the high expression of CXCR4 in aldosterone-producing adrenal tumors is closely associated with the expression of CYP11B2 (aldosterone synthase).…”
Section: Figurementioning
confidence: 99%
“…CXCR4 is expressed by a variety of inflammatory and malignant cells 6 . Therefore, in vivo quantification of CXCR4 expression using CXCR4-targeted PET/CT imaging has received some consideration 7–9 . Recently, a growing literature has reported that 68 Ga-pentixafor PET/CT plays an important role in the diagnosis of some tumors and inflammation 10–12 .…”
mentioning
confidence: 99%